MEDICINAL PLANTS IN THE MANAGEMENT OF CLIMACTERIC AND MENOPAUSAL SYMPTOMS: A REVIEW - Borcard, Guiomar Godinho; Vieira, Glauciemar Del-Vechio; Santos, Bruna Celeida Silva; Oliveira de Lucas Xavier, Julianna; Santos de Matos Araújo, Ana Lúcia; Vieira de Sousa, Orlando (Acta Biologica Brasiliensia, 2025)
Climacteric, the hormonal transition phase that precedes and leads to menopause, is characterized by physical and emotional symptoms that can be alleviated through the use of phytotherapy. This study conducted a literature review on the use of such medicinal plants in managing climacteric and menopausal symptoms, drawing from databases such as PubMed, Scopus, SciELO, Web of Science, Google Scholar, IEEE Xplore, as well as government sources, using specific keyword combinations. Plant species such as Cimicifuga racemosa, Trifolium pratense, Glycine max, Angelica sinensis, Vitex agnus-castus, Panax ginseng, Lepidium meyenii, and Morus nigra have shown significant benefits. Their active compounds act on estrogen, serotonin, and dopamine receptors, exhibiting hormonal, anti-inflammatory, antioxidant, adaptogenic, immunomodulatory, and calming effects. These actions contribute to the relief of symptoms such as hot flashes, insomnia, anxiety, irritability, inflammation, mood and cognitive changes, vaginal dryness, fatigue, and low libido, while also promoting bone and cardiovascular health and hormonal balance. Thus, the use of medicinal plants with phytoestrogenic activity stands out as a promising and effective complementary approach to supporting women’s health during the climacteric and menopausal periods.